SOLUTIONS OF USING PEDAGOGICAL TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING - Norbekova, Rano (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT SOLUTIONS OF USING PEDAGOGICAL TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING